Perbandingan Aktivitas Antioksidan pada Ekstrak Murni, Granul dan Tablet Effervescent Ekstrak Kulit Manggis (Garcinia mangostana L.) - Feronika Evma Rahayu; Fenny Sandriyani; Aluwi Nirwana Sani (Jurnal Farmasi Indonesia, 2024)
The mangosteen rind (Garcinia mangostana L.) contains alkaloids, flavonoids, triterpenoids, tannins, and polyphenols. Flavonoids are secondary metabolites found in it which act as antioxidants. Research on antioxidant activity testing with samples of pure extract, effervescent granules, and effervescent tablets from mangosteen rind extract was conducted to determine the antioxidant content in each formulation. The extraction method used in the study was maceration with 96% ethanol solvent followed by rotary evaporation and water bath at 40°C to obtain a concentrated extract. The yield of the extract was 23.4%, meeting the criteria for a good extract. The concentrated extract was then dried in an oven at 40°C to obtain dry extract. Subsequently, phytochemical screening of the mangosteen rind extract was performed to identify the secondary metabolites present. Antioxidant activity testing was conducted using the DPPH method with methanol as the solvent and quercetin as the positive control. The strongest IC50 value was found in the pure mangosteen rind extract with a value of 0.037 ppm, followed by the effervescent granules with an IC50 value of 0.607 ppm, and the effervescent tablets with an IC50 value of 2.517 ppm. A smaller IC50 value indicates a higher antioxidant capacity in scavenging free radicals.